Microsatellite primer resource for Populus developed from the mapped sequence scaffolds of the Nisqually-1 genome - Yin, T M (The New phytologist, 2009)
In this study, 148 428 simple sequence repeat (SSR) primer pairs were designed from the unambiguously mapped sequence scaffolds of the Nisqually-1 genome. The physical position of the priming sites were identified along each of the 19 Populus chromosomes, and it was specified whether the priming sequences belong to intronic, intergenic, exonic or UTR regions. A subset of 150 SSR loci were amplified and a high amplification success rate (72%) was obtained in P. tremuloides, which belongs to a divergent subgenus of Populus relative to Nisqually-1. PCR reactions showed that the amplification success rate of exonic primer pairs was much higher than that of the intronic/intergenic primer pairs. Applying ANOVA and regression analyses to the flanking sequences of microsatellites, the repeat lengths, the GC contents of the repeats, the repeat motif numbers, the repeat motif length and the base composition of the repeat motif, it was determined that only the base composition of the repeat motif and the repeat motif length significantly affect the microsatellite variability in P. tremuloides samples. The SSR primer resource developed in this study provides a database for selecting highly transferable SSR markers with known physical position in the Populus genome and provides a comprehensive genetic tool to extend the genome sequence of Nisqually-1 to genetic studies in different Populus species